Preparation of Tannin Based Hydrogel for Biological Application - R. Jameel Mhessn; L. Abd-Alredha; R. Al-Rubaie; A. Fuad Khudair Aziz (E-Journal of Chemistry)
Polymeric blends as potential wound dressing were prepared. Natural polymer (Tannin) and synthetic polymers (PVA and PEG) were used to prepare heterogeneous blends. The product was identified by spectrophotometry. A diaphragm cell was used to measure the diffusion coefficient (D). The result shown the PEG-PVA disk was very faster permeability for all solution. The D of PVA/ PEG-Tannin blend was 0.184x10-3 cm2/s higher than Tannin-PEG blend was 0.038x10-3 cm2/s. The natural phenolic compounds that can be used artificial membrane to inhibit growth or kill microorganism such as bacteria or fungi.